National evaluation of Safe Start Promising Approaches : assessing program outcomes - Jaycox, Lisa.; Hickman, Laura J.; Schultz, Dana J.; Barnes-Proby, Dionne; Setodji, Claude Messan; Kofner, Aaron; Harris, Racine S.; Acosta, Joie D.; Francois, Taria; Rand eBooks (Santa Monica, CA : RAND, 2011)
Safe Start Promising Approaches (SSPA) is the second phase of a community-based initiative focused on developing and fielding interventions to prevent and reduce the impact of children$1 (Bs exposure to violence (CEV). This report shares the results of SSPA, which was intended to implement and evaluate promising and evidence-based programs in community settings, and includes all data available in the project, updating an earlier report. Fifteen program sites across the country were selected to implement a range of interventions for helping children and families cope with the effects of CEV. The settings, populations served, intervention types, types of violence addressed, community partners, and program goals differed across the 15 sites. The main body of this report provides information on the designs of the studies, instruments used, data collection and cleaning, analytic methods, and an overview of the results across the 15 sites. The appendixes provide a detailed description of the outcome evaluation conducted at each SSPA program, including a description of the enrollees, enrollment and retention, the amount and type of services received, and child and family outcomes over time.s
"RAND Health and Infrastructure, Safety, and Environment."
"This research was conducted under the auspices of the Safety and Justice Program with RAND Infrastructure, Safety, and Environment (ISE) and under RAND Health's Health Promotion and Disease Prevention Program."
Includes bibliographical references (p. 59-63).
Also available on the internet via WWW in PDF format.
Keywords: Safe Start Promising Approaches (Program) -- Evaluation; Child welfare -- United States; Children and violence -- United States -- Prevention; Children -- Services for -- United States -- Evaluation; Electronic books